Gypscie-KG: Building a Logic-Based Approach for Knowledge Graph Data Integration View in ML Systems - Moraes, Gabriela; Porto, Fabio; Ulliana, Federico; Baget, Jean-François; Leclère, Michel; Bisquert, Pierre; Gonçalves, Bernardo; Valduriez, Patrick (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD); 2025: Anais Estendidos do XL Simpósio Brasileiro de Bancos de DadosDO - 10.5753/sbbd_estendido.2025.248170, 2025)
This paper presents Gypscie-KG, a system that integrates heterogeneous machine learning (ML) data into a knowledge graph (KG) using logicbased rules to enable semantic queries and reasoning. It also explores the use of ChatGPT to support relational-to-graph schema mapping, demonstrating AI’s potential in declarative data integration for complex ML systems.